Pembuatan Direktori Wisata di Kota Bukittinggi dan Kabupaten Agam - Yova, Wiya Efrina; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2017)
This paper discusses the making of tourist directory of Bukittinggi and Agam.The preparation of this directory aims to create a product that can help users find information related to tourism in the City of Bukittinggi and Kabupaten Agam.The method used in the writing of this paper are the observation, interview and literature study to determine the sights and explanations about what is contained in existing attractions in the City of Bukittinggi and Agam District.Based on the discussion, It concluded that there was 14 tourist attractions in the city of Bukittinggi and 12 attractions in Agam District.The steps in the manufacture of directories are as follows: (a) determine of the subject by finding answers to the question what or who was expressed in a sentence, and the book.Usually,Â  the subject of the book usedÂ  the question word â€œwhatâ€;(B) classify / group data collected in accordance with the subject which has been determined based on the title classification, then the title of the developer into several parts arranged according to the group;(c) prepareÂ  a directory that begins with making the cover, preface, table of contents, and the contents and the cover of the directory.Keywords: direktory, tour.Â